Percepções dos agentes comunitários de saúde de Belo Horizonte sobre Tuberculose e tratamento - Kennedy Crepalde Ribeiro (2015)
Tuberculosis is a major challenge for public health. Brazil is among the 22 countries with the highest tuberculosis burden. In order to increase patient adherence to tuberculosis treatment, it was created the directly observed treatment. The community health worker is one of the pillars in tuberculosis control and supervision of treatment, due to his/her performance and experience in the field. It was intended with this study to understand the perceptions of these professionals on the tuberculosis and treatment. A semi-structured and self-administered questionnaire with closed and open questions was applied to 489 community health workers from 37 health centers in every region of Belo Horizonte. The survey collection took place from July to December 2013. For the present study, we analyzed the open-ended questions, which addressed the facilitators and difficulties for the supervision and suggestions to improve adherence to treatment. A qualitative approach through thematic content analysis and interpretation of the results based on the Social Representation Theory. Of the 428 participants who responded to open-ended questions, more than 90% were women, 51.5% worked for six years or more and 51.2% had conducted the supervision. Five categories were obtained: intrinsic factors of health system; intrinsic factors of community health workers in directly observed treatment execution; aspects and outcomes related to tuberculosis treatment; intrinsic factors of patients and their sociocultural context, and empowerment as an instrument for change. The implementation of the directly observed treatment in Brazil was an improvement and community health workers are an important role in the strategy. However, challenges remain such as work overload, deficiencies in the professional training process, social vulnerability and embarrassment to certain patients. Stigma interferes with treatment once home visits could reveal the diagnosis. Facing a complex challenge, professionals eventually choose to use the oppressive state power, such as the compulsory hospitalization. Many participants considered, mistakenly, that adherence is influenced mostly by patient-related factors. A greater freedom in the choice of the responsible for supervision may be important in order to increase convenience and compliance. Popular education in health can also contribute to empower and motivate those 8 involved. The flexibility of the workers routine should also be considered for improving health care.